Uderstanding The Partnership Landscape For Renewable Energy Development In Indonesia - Iqbal Akbar (Jurnal Universitas Paramadina, 2017)
Renewable energy development in Indonesia is still young compared to its sister sector, the upstream oil and gas sector, which have invited many investors to develop the market. As the commitment for COP 21 Paris, Indonesia is bounded to develop the renewable energy sector to provide a cleaner energy source and reduce CO2 emission via various national programs. The formal partnership has become the prominent model for engaging various stakeholders; the government, non-government organization, private sector, academia, local community, etc. Through a closer look to the dynamic of the regulatory framework, this article presents different cases of partnership in the renewable energy sector in Indonesia while at some point benchmarking to the similar development in other countries and its sister sector. The study shows that the formal partnership model in the form of PPP is suitable for the large-scale power systems while 5P is suitable for small-scale and decentralised power systems. Conclusions and recommendations of how the mission-oriented partnership is narrated to strengthen Indonesia's renewable energy development roadmap is drawn at the end.